Batch and column studies of phosphate and nitrate adsorption on waste solids containing boron impurity - Olgun, A.; Atar, Necip; Wang, Shaobin (Elsevier BV, 2013)
In the present study, we investigated the removal characteristics of phosphate and nitrate through adsorption on boron waste (BW) and heat treated boron waste (BW400) under batch equilibrium and column flow conditions. The effects of pH, contact time, initial solution concentration, and temperature on the uptake of both anions by the adsorbents in batch operation were examined. The equilibrium data were fitted to different types of adsorption isotherms. Langmuir adsorption model showed the best fit to the experimental adsorption data. The data were further analyzed on the basis of the Lagergren first order, pseudo-second-order and intraparticle diffusion kinetic models. The maximum adsorption capacities of heat treated BW for nitrate and phosphate were approximately 63.2 and 52.5 mg g-1, respectively, which shows higher maximum capacity for phosphate and a similar capacity for nitrate in comparison with other adsorbents used. Breakthrough curves obtained from fixed-bed column tests showed that column adsorption capacities provided strong evidence of the potential of BW400 for the technological applications of phosphate and nitrate removal from aqueous solutions.